IMPLEMENTASI MOTOR BLDC 350W UNTUK MENINGKATKAN KECEPATAN PENGGULUNGAN SELANG PEMADAM KEBAKARAN - Putra, Mochamad Wildan Karyono; Anshory, Izza; Sulistiyowati, Indah; Saputra, Dwi Hadidjaja Rasjid (Rang Teknik Journal, 2025)
The effective management of fire hoses is critical for ensuring rapid and efficient response in emergency situations. This study explores the implementation of a 350W Brushless DC (BLDC) motor for improving the speed and efficiency of fire hose retraction systems. The research aims to enhance the performance of fire hose reels by replacing conventional methods with a more advanced motor-driven system. The methodology involves an experimental approach with phases including design, implementation, testing, and data analysis. The system was evaluated under various conditions, including both unloaded and loaded states with water. Results indicate that while the BLDC motor significantly improves retraction speed compared to conventional methods, its performance is affected by additional load, showing the need for further optimization. This research contributes to the development of more efficient fire safety equipment, providing valuable insights into the integration of advanced motor technologies in critical response systems. Keywords: Brushless DC Motor, Fire Hose Retraction, Motor Efficiency, Fire Safety Equipment, Experimental Evaluation, Load Testing